PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI USAHA PENGOLAHAN KERIPIK SINGKONG DALAM MENCIPTA LAPANGAN KERJA PADA MASA PANDEMI DI DUSUN RAYUD DESA PARIJATAH KULON KECAMATAN SRONO KABUPATEN BANYUWANGI - Ainur Rofiq; Nasrodin Nasrodin (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2022)
This research originates from the economic conditions of the people of Rayud Hamlet, Parijatah Kulon Village, which have experienced an increase in the business of processing cassava chips due to the large number of people who grow cassava. This study aims to determine the process of family economic empowerment in Rayud Hamlet, Parijatah Kulon Village. Retrieval of data using survey or observation methods. The population of this study is the entire community of Rayud Hamlet, Parijatah Kulon Village, so the focus of the sample in this study is micro, small and medium enterprises in Rayud Hamlet using the census method. To find out the general description of family economic empowerment businesses used descriptive analysis, to find out the income of the cassava chips business used income analysis, and to find out the relative profits used R/C Ratio analysis. The results showed that the process of empowering the family economy through increasing the cassava chip processing business was successfully carried out with the following strategies: 1) assistance to increase the cassava chip business in terms of labeling and packaging so as to simplify the marketing process; 2) recruit residents to become employees; 3) sufficient customer demand. So that the results or income of the cassava chips business increased by Rp. 8,505,000 per month, with working hours not more than 5 hours per day. So that the value of R/C Ratio > 1 means that it is economically profitable and the cassava chip business is feasible to become a medium for family economic empowerment.